Technology Integration in Community Service: Empowering IDX Employees with Data Visualization Skills - Wirda Andani; Hendra Perdana; Nurfitri Imro'ah; Evy Sulistianingsih; Neva Satyahadewi; Ray Tamtama; Shantika Martha; Yuyun Eka Pratiwi; Pitriani Pitriani; Annisa Auliarahmi; Muhammad Fikri (Universitas Ahmad Dahlan, 2026)
Background: The rapid growth of digitalization in the capital market requires the Indonesia Stock Exchange (IDX) to deliver transparent, accurate, and understandable information through data visualization. However, employees at the IDX West Kalimantan Representative Office rarely process and visualize data, even though it is essential for carrying out daily tasks. Contribution: This study fills the gap in technology-based community service programs that rarely integrate infographic training with information literacy enhancement in capital market education. The novelty of this study lies in the evaluation of the community service program, which not only measures the effectiveness of the training but also employs CB-SEM to identify the factors influencing participants’ learning outcomes. Method: The Statistics Study Program, Untan, conducted a training workshop combining theory and practice with real data. A situational analysis with IDX representatives was first carried out to identify needs and design the program. Effectiveness was evaluated using pre-tests, post-tests, and satisfaction surveys. Results: The paired t-test results at the 5% significance level demonstrating the effectiveness of infographic training in enhancing data visualization skills. In addition, CB-SEM analysis revealed that the module variable was the dominant factor, highlighting the importance of structured and relevant training materials in supporting participants’ learning outcomes. Conclusion: The training effectively enhanced the knowledge and skills of IDX West Kalimantan Representative employees in data processing and visualization.